2022
DOI: 10.1152/japplphysiol.00171.2021
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the metabolic reductions of a passive back-support exoskeleton

Abstract: Despite several attempts to quantify the metabolic savings resulting from the use of passive back-support exoskeletons (BSEs), no study has modeled the metabolic change while wearing an exoskeleton during lifting. The objectives of this study were to: 1) quantify the metabolic reductions due to the VT-Lowe's exoskeleton during lifting; and 2) provide a comprehensive model to estimate the metabolic reductions from using a passive BSE. In this study, 15 healthy adults (13M, 2F) of ages 20 to 34 years (mean=25.33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…If exoskeletons decrease the metabolic energy required to perform repetitive lifting by up to 12% (e.g. as was shown in [84]- [86]), management may assume that workers should be able to utilize that saved energy to work harder or faster, accomplishing more in a given amount of time. However, this logic fails to consider how the work is distributed throughout the worker's body.…”
Section: Overuse and Overworkmentioning
confidence: 99%
“…If exoskeletons decrease the metabolic energy required to perform repetitive lifting by up to 12% (e.g. as was shown in [84]- [86]), management may assume that workers should be able to utilize that saved energy to work harder or faster, accomplishing more in a given amount of time. However, this logic fails to consider how the work is distributed throughout the worker's body.…”
Section: Overuse and Overworkmentioning
confidence: 99%
“…For instance, studies have repeatedly shown that back exos reduce muscle strain and spinal compression forces, which are risk factors for low back pain and overuse injury (Kermavnar et al, 2020 ; Lamers and Zelik, 2021 ). Back exos have also been observed to reduce muscle fatigue (Lamers et al, 2020 ; dos Anjos et al, 2022 ) and metabolic rate (Baltrusch et al, 2019 ; Alemi et al, 2022 ; Schmalz et al, 2022 ) during bending and lifting tasks, which could enhance endurance or other performance outcomes during physical tasks. Much of the scientific evidence on exos has been generated over the last decade in laboratory experiments or controlled field studies (Kermavnar et al, 2020 ; Crea et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%